Toxic Effects of Fungicides (Penconazole and Triadimenol) on Growth and Protein Amount of Scenedesmus acutus - Agirman, Nur; Bedil, Burcin; Kendirlioglu, Gokce; Cetin, Ahmet Kadri (Chem Soc Pakistan, 2015)
In this work, the effects of penconazole and triadimenol to protein amount and growth of the microalgae Scenedesmus acutus were investigated. The culture of S. acutus was exposed to dissimilar concentrations of penconazole and triadimenol (1, 3, 6, 10 and 15 mu g/L) in the climate chamber at 23 +/- 1 degrees C and 16:8 photoperiod. Cell numbers and growth rates in liquid cultures of S. acutus were calculated for a period of four days. The results indicated toxic effects of penconazole and triadimenol on growth and protein amount of S. acutus. The protein amount and cell number of S. acutus in cultures treated with penconazole and triadimenol were rapidly decreasing at second day.
Keywords: Scenedesmus acutus; Penconazole; Triadimenol; Protein amount; Cell growth